Imagen corporativa de los productos finales presentados en la carrera de ingeniería agroindustrial de la Universidad Técnica Estatal de Quevedo, año 2016. Propuesta de diseño - Armijos Loor, Dayana Lisseth (2016)
This research was carried out at the Quevedo State Technical University of Quevedo, Province of Los Ríos, located in the sector Av. Quito Km 11/2 Via Santo Domingo de los Tsáchilas. The General Objective that was proposed was to design the corporate image of the final products presented at the Agroindustrial Engineering Career of the Quevedo State Technical University, which allows to project confidence towards the university community. Students in the agro-industrial career produce innovative food products that lack a corporate image that helps them identify with the public. The methods applied in the investigation were the inductive, deductive and analytical that allowed to obtain valid and original information that was analyzed to know and deepen the subjects of investigative studies and to carry out the fulfillment of the objectives and to carry out the development of the manual of corporate image for the End products of the race. Two surveys were applied, one to the UTEQ population and another to the students of the agroindustrial career. With which several criteria were known, which are valid for the development of the manual of corporate image the same one that counts on a series of instructions like the catacterísticas that must have a label, a good presentation, colors, typography and the correct use of the brand. In addition, an interview was conducted with the race coordinator to find out what types of products the students were producing, which were categorized by food and non-food products and thus know their current situation. The development of the corporate image manual will allow the visual presentation of the final products to be recognized and identified by the public and will be of benefit to the industrial career, with the knowledge of an own and visible image.